RELEVANSI BUDAYA PENDIDIKAN YAHUDI ZAMAN PERJANJIAN LAMA BAGI SISTEM PENDIDIKAN KRISTEN MASA KINI - Jimmy Rungkat (Politeknik Amamapare, 2025)
This research aims to examine education in Old Testament Jewish culture in order to find the essence of its important principles as relevant to today's Christian education system. Through the descriptive qualitative method using a literary and hermeneutic Biblical study approach in finding theological meanings of the Biblical text related to the topic of discussion, the results were obtained that education in Old Testament Jewish culture was very strong with the role of the family in educating children using material taught from educational institutions or from practical educational material in the family. This learning process is delivered both within a theoretical and practical framework for everyday life. All of this is done as a form of love and at the same time in embodying God's Torah. The characteristic of education in Jewish culture is that it is practiced with love, carried out continuously, based on the Word of God, and always pays attention to students. Education in Old Testament Jewish culture is very relevant for today's Christian education to educate students comprehensively in order to produce individuals with divine character and a positive impact on others, with the principles of theocentric Christian education, education with a logical-theological thinking system must be the foundation, education in the family becomes second place after school, and education using firm and measurable methods is still necessary.